Cosmetics & toiletries formulations database - Flick, Ernest W. (Norwich, NY : William Andrew Pub., 2005)
More than 10,000 formulations are included. The database comprises the 8 print volumes by Ernest Flick together with thousands of updated and new formulas. All formulations contain a listing of ingredients and their percent weight. Most formulations also contain the suggested formulation procedure. The database is divided into 16 broad categories: Antiperspirants and Deodorants, Baby Products, Bath and Shower Products, Beauty Aids, Creams, Fragrances and Perfumes, Hair Care Products, Insect Repellents, Lipsticks, Lotions, Shampoos, Shaving Products, Soaps and Hand Cleaners, Sun Care Products, Toothpastes, and Miscellaneous.
Keywords: Cosmetics; Toilet preparations